Crystal engineering applied to pharmaceutical antihypertensives to improve their physical chemical properties - Firmino, Pollyana Pereira (2025)
The thesis addresses the problem of arterial hypertension (AH), which affects more than a third of the world\'s population. As it is a chronic disease, it requires treatment that usually involves medications and changes in lifestyle habits. However, in two-thirds of cases, monotherapy is not enough, highlighting the need for more technological drugs. Knowing that oral administration of drugs in solid form is prevalent, the development of quality Active Pharmaceutical Ingredients (APIs) solid forms is essential. Crystal Engineering emerges as a strategy to optimize physicochemical properties by exploiting intermolecular interactions to modulate properties such as melting point, hygroscopicity, solubility and permeability. Its application in the production of new solid forms represents an attractive alternative for the Pharmaceutical Industry, allowing the rational planning of APIs with improved properties. Most antihypertensive drugs in Brazil, as well as in the world, face problems of solubility and/or permeability, emphasizing the importance of innovative approaches. The thesis seeks to plan, obtain and characterize new solid forms of antihypertensive APIs. Here, six new solid forms published in articles and patents are presented and characterized: free Hydralazine, Hydralazine hydrobromide and nitrate, cocrystals of Hydrochlorothiazide with L-proline and 5-Fluorocytosine, and the cocrystal of chlorthalidone and theobromine presented in chapter 4, from which significant results were obtained in terms of improving the solubility of the API. These results led to the publications of two scientific articles in international indexed journals, as well as the application of four patents. These results show the improvement of physicochemical properties of the new solid forms, providing valuable insights for the pharmaceutical industry and contributing to professional and scientific development through international collaborations.